A Meta-analytic Approach for Testing Evolutionary Hypotheses of Acquired Resistance in Metastatic Cancer - Bhardwaj, Kalpana (Université d'Ottawa / University of Ottawa, 2014)
Nowell (1976) first proposed that unless cytotoxic cancer therapy eradicates all tumor cells, genetic or heritable variation within heterogeneous tumors will inevitably lead to the evolution of chemotherapeutic resistance through clonal selection. This evolutionary hypothesis was formalized by Goldie and Coldman (1979), who developed one of the earliest mathematical kinetic models of resistance evolution in neoplasms. Their model predicted that the likelihood of response and cure would be increased in combination vs single agent cytotoxic therapies. In a later study, Gardner (2002) developed a computational kinetic model to predict chemotherapeutic combinations, doses, and schedules most likely to result in patient response and prolonged life. This model predicts that combination therapy involving both cytotoxic and cytostatic drugs will be more effective than combination therapy involving only cytotoxic drugs. Thus far, no systematic evaluation of the Goldie and Coldman and Gardner hypotheses have been conducted in the metastatic clinical trial setting. Here I test these hypotheses using the results of over 700 phase II, III and II/III clinical trials. I show that, as predicted by Goldie and Coldman, both overall response rate and overall survival were greater in combination arms. Moreover, median duration of response – the key indicator of the rate of resistance evolution - was also greater in combination vs single agent arms. These results suggest that generally combination chemotherapy is more effective than single agent therapy for advanced solid tumors as predicted by Goldie and Coldman (1979) hypothesis and that, at least in the metastatic setting, the potential disadvantages of combination therapy with respect to accelerated resistance evolution are outweighed by the greater waiting times for resistance mutations to arise. By contrast, although combination cytotoxic and cytostatic therapy is associated with a greater average overall response rate than multi agent cytotoxic therapy, this is not the case for both median duration of response and overall survival. Hence, there is no evidence that, in contrast to the predictions of the Gardner (2002) model, combination cytotoxic and cytostatic therapy decreases the rate of resistance evolution relative to that obtaining under combination cytotoxic therapy.
Keywords: cancer; resistance evolution; chemotherapy; meta-analysis; combination therapy; monotherapy; clinical trial